Perspective of usage of cluster computers in aviation - Жуков, И. А.; Гуменюк, A. B. (Proceedings of National Aviation University (archive), 1999)
Considered are the problems of application of highly effective computer systems in aviation and principles of cluster computer systems construction. Presented are the examples of their usage and perspectives of development